Reef Rescue Marine Monitoring Program synthesis report 2010-2011 - Martin, K.C.; McKenzie, L.J.; Thompson, A.; Muller, J.; Bentley, C.; Paxman, C.; Collier, C.; Waycott, M.; Brando, V.; Devlin, M.; Schaffelke, B. (Great Barrier Reef Marine Park Authority, 2014)
The Reef Rescue Marine Monitoring Program Synthesis report summarises the monitoring methods and results used in the Program including inshore water quality, pesticides, coral and seagrass monitoring.
Keywords: Water quality; Sampling techniques; Pesticides; Coral; Inshore waters; Coasts; Water quality